Influence of Pulsed DC Sputtering Power on the Quality and Residual Stress of AlN Films on Si (100) Substrates. Issue 5 (27th February 2022) - Yin, Haotian; Han, Jun; Xing, Yanhui; Deng, Xuguang; Cheng, Wei; Zhang, Yao; Guan, Baolu; Zhang, Baoshun
Abstract: Aluminum nitride (AlN) films are prepared on Si (100) substrates by pulsed direct current magnetron sputtering. The effect of sputtering power on the crystal quality, residual stress, surface morphology, and optical properties of AlN films is comprehensively studied using X‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), atomic force microscope, and ellipsometer. It is found that the AlN film quality is strongly impacted by the sputtering power. When the sputtering power increases to 3 kW, the full width at half maximum of the AlN (002) rocking curve decreases to 2.66°. And the film crystal quality does not change significantly when the sputtering power exceeds 3 kW. Fourier transform infrared spectrum analysis shows that with increasing sputtering power, the compressive stress of AlN films first increases and then decreases. The high sputtering power also results in smoother surface and better optical performance for the AlN films. This work can serve as an important reference for growing high‐quality AlN films on cost‐effective silicon (Si) substrates via sputtering, which can facilitate the development and commercialization of III‐nitride based photonics and electronics on AlN‐on‐Si substrates. Abstract : Aluminum nitride (AlN) has great application potential in microelectronic devices. It is very important to study the methods to improve the performance of AlN. The crystal quality, residual stress, surface morphology, and optical properties of sputtered AlN films on Si (100) substrate are improved by changing the sputtering power. The influence mechanism of pulsed DC sputtering power is analyzed.